Rift propagation signals the last act of the Thwaites Eastern Ice Shelf despite low basal melt rates - Christian T. Wild; Samuel B. Kachuck; Adrian Luckman; Karen E. Alley; Meghan A. Sharp; Haylee Smith; Scott W. Tyler; Christopher Kratt; Tiago S. Dotto; Daniel Price; Keith W. Nicholls; Suzanne L. Bevan; et al. (Journal of Glaciology)
Rift propagation, rather than basal melt, drives the destabilization and disintegration of the Thwaites Eastern Ice Shelf. Since 2016, rifts have episodically advanced throughout the central ice-shelf area, with rapid propagation events occurring during austral spring. The ice shelf's speed has increased by ~70% during this period, transitioning from a rate of 1.65 m d−1 in 2019 to 2.85 m d−1 by early 2023 in the central area. The increase in longitudinal strain rates near the grounding zone has led to full-thickness rifts and melange-filled gaps since 2020. A recent sea-ice break out has accelerated retreat at the western calving front, effectively separating the ice shelf from what remained of its northwestern pinning point. Meanwhile, a distributed set of phase-sensitive radar measurements indicates that the basal melting rate is generally small, likely due to a widespread robust ocean stratification beneath the ice–ocean interface that suppresses basal melt despite the presence of substantial oceanic heat at depth. These observations in combination with damage modeling show that, while ocean forcing is responsible for triggering the current West Antarctic ice retreat, the Thwaites Eastern Ice Shelf is experiencing dynamic feedbacks over decadal timescales that are driving ice-shelf disintegration, now independent of basal melt.